Proteomics Analysis Reveals Altered Nutrients in the Whey Proteins of Dairy Cow Milk with Different Thermal Treatments - Yangdong Zhang; Li Min; Sheng Zhang; Nan Zheng; Dagang Li; Zhihua Sun; Jiaqi Wang (Molecules, 2021)
Thermal treatments of milk induce changes in the properties of milk whey proteins. The aim of this study was to investigate the specific changes related to nutrients in the whey proteins of dairy cow milk after pasteurization at 85 °C for 15 s or ultra-high temperature (UHT) at 135 °C for 15 s. A total of 223 whey proteins were confidently identified and quantified by TMT-based global discovery proteomics in this study. We found that UHT thermal treatment resulted in an increased abundance of 17 proteins, which appeared to show heat insensitivity. In contrast, 15 heat-sensitive proteins were decreased in abundance after UHT thermal treatment. Some of the heat-sensitive proteins were connected with the biological immune functionality, suggesting that UHT thermal treatment results in a partial loss of immune function in the whey proteins of dairy cow milk. The information reported here will considerably expand our knowledge about the degree of heat sensitivity in the whey proteins of dairy cow milk in response to different thermal treatments and offer a knowledge-based reference to aid in choosing dairy products. It is worth noting that the whey proteins (lactoperoxidase and lactoperoxidase) in milk that were significantly decreased by high heat treatment in a previous study (142 °C) showed no significant difference in the present study (135 °C). These results may imply that an appropriately reduced heating intensity of UHT retains the immunoactive proteins to the maximum extent possible.